FTY720 in combination with cyclosporine - an analysis of skin allograft survival and renal function - Silva, Francieli Ruiz; Lucas Silva, Lea Bueno; Cury, Patricia Maluf; Burdmann, Emmanuel Almeida; Bueno, Valquiria (Elsevier B.V., 2006)
Acute and chronic nephrotoxicity caused by CsA Continuous administration impair kidney allograft survival. Several clinical and experimental protocols have shown benefits to the kidney after decreasing CsA dose, withdrawing the drug or delaying its introduction after transplantation.FTY720 is a new Compound that has immunosuppressive characteristics and increase allograft survival in animal models without causing the side effects of calcineurin inhibitors (CNIs). FTY720 described mechanism of action that consists to alter the lymphocyte migration pattern without impairment of the immune system response against pathogens.In our mice model, FTY720 administered alone or in combination with CsA during 21 days increased skin allograft survival in a fully mismatched strain combination and did not cause significant changes in renal function. Moreover, renal structure was normal in all groups suggesting that at low doses (10 mg/kg/day) CsA can be associated during short-term period to other immunosuppressive drugs, i.e. FTY720 without affecting the kidney.Combination of immunosuppressive compounds with FTY720 and/or delayed introduction of low cyclosporine dose Could prevent graft rejection and avoid nephrotoxicity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: transplantation; immunosuppression; renal function; T lymphocytes